PERAN PANTI ASUHAN DALAM MELAKSANAKAN FUNGSI PENGANTI KELUARGA ANAK DI PANTI ASUHAN MANDE KANDUANG - Lisa Oktavia; Hidayani Syam (CV. ADIBA AISHA AMIRA, 2024)
The aim of this research is to determine the role of the Orphanage in carrying out the function of replacing the families of foster children at the Mande Kanduang Orphanage. The focus of this research is to provide protection for foster children, to fulfill children's rights in survival and to support children's personality development in which there are inhibiting factors. Source of data taken at the Mande Kanduang Orphanage. The data analysis used in this research is descriptive qualitative data analysis, namely describing what happens in the field